The direction of the changes of rates of the internal and external training load under the influence of high-altitude hypoxia on mountain bikers - Gabrys, T.; Szmatlan-Gabrys, U.; Stanula, A. (Physical Activity Review, 2019)
The aim of the research carried out was to establish the direction, and scope of the changes in internal, and external load indicator values in cyclists, men, and women, in high-altitude hypoxia conditions. The participants of the study were mountain bike cyclists, members of Russian and Polish Nationals Teams (women n=11, men n=9). They have done the graded incremental exercise test at the altitude of 170 m (Lonato del Garda, Italy) and 2250 m (Livignio-Trepale Italy). In the course of effort VO2, VE, VCO2 was measured by means of K4b2 analyser (Cosmed Italy). Effort intensity was determined at ventilators thresholds VT1 (AT), and VT2. Internal and external load indicators undergo changes during physical effort in cyclists under the influence of high altitude hypoxia. In groups of men and women, the changes in indicator values reach VE: 9% and 12%, HR: 0,5% and 15, O2HR: 7% and 15%, VO2: 14% and 20% respectively, as well as a decrease in 5 and 4% of the generated power, respectively. A decrease in the generated power by 5%, higher ventilation, amounting to 10%, a higher VO2max, amounting to 17% in hypoxic conditions, in comparison with the conditions similar to those at sea level, show that it is necessary to modify training loads.